Pelatihan Tata Kelola Barang Milik Daerah Kabupaten Toraja Utara untuk Mendukung Akuntabilitas - Agus Bandang; Andi Kusumawati; Darmawati Darmawati (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
Effective management of Regional Property (Barang Milik Daerah/BMD) is a critical component in achieving financial accountability and Good Governance in local governments. However, audit findings by the Supreme Audit Agency (BPK) consistently reveal weaknesses in BMD recording, inventory, and reporting due to limited officer capacity and delayed implementation of updated regulations. This community service activity aimed to improve the capabilities of BMD managers in Toraja Utara Regency through structured training and applied mentoring. The activity employed a participatory approach, comprising needs assessment, module development, intensive training, and pre-post evaluation. Implemented on November 21, 2025, the training involved 25 BMD managers from various SKPDs. Results showed a significant increase in participants’ understanding of Permendagri No. 47/2021, SAP compliance, KIB preparation, and systematic reporting. A comprehensive training module was successfully distributed as a long-term reference. The activity successfully strengthened the technical capacity of local apparatus, supporting more transparent, accountable, and audit-ready BMD management.